Objeto-imagem: [entre]meios de uma poética - Calderan, Odete Angelina (2011)
The present research in visual arts has proposed to investigate, so practical and theoretical, the process of a series of poetic works, seeking to establish new relationships in order to propose a dialogue between language and means ceramic photographic and videography. We suggest the combination of digital resources as agents for trial between languages, materials, techniques and support of hybrid possibilities. From these choices, resize to the ways in different contexts of displacement: at first, in the studio pottery, in a second stage, in a meeting place - the existing Pottery Campus UFSM - seen as potential place-image, in a third time, it operates with the place of exposure and assemblages (interaction) in its surroundings. Such possibilities are experienced in all the poetic works, build relationships of proximity, specific conceptual and procedural and present intertwine in research, helping to contextualize the practice. Thus, the series production facilities Between Ball 1, 2 Between Spheres, Balls Between 3 and artistic proposals A Whole in Parts I, II and III proposed relationships, travels, crosses and associations, establishing new roads and contributing to the poetic research contemporary art.